MENGUAK RELEVANSI KETENTUAN GRATIFIKASI DI INDONESIA - Topo Santoso (Faculty of Law, Universitas Jenderal Soedirman, 2013)
Gratification is defined as a gift in broad meaning, which cover money, goods, discount, commision, loan without interest, travel ticket, accomodation facility, tour travelling, free health service, and other facilities. The issue is that many institutions have used definion of gratification provided in Law No.20 of the Year 2001 to regulate ethical code in the institutions. This is interesting because the definition in the Law deal with criminal offence while definition in the ethical code deal with ethical violation. Sincronization is needed to differentiate between gratification in criminal law perspective and ethical perspective. Key words: gratification, corruption, KPK